Desenvolvimento de ferramentas biotecnológicas a partir de recursos naturais para o tratamento da doença de Alzheimer - Santos, Rosiane dos (2013)
Alzheimer´s disease (AD) is a neurodegenerative disorder responsible for the largest number of cases of dementia in the elderly. The brain regions associated with the frontal cortex and the hippocampus are the most affected by the changes arising from the AD, resulting in loss of neuronal function, and the loss of memory and cognitive ability. In the cellular level, AD is associated with reduced levels of acetylcholine (ACh) in the synaptic process, decreasing cortical cholinergic neurotransmission. ACh is a neurotransmitter found in the brain and at(in the) neuromuscular junctions, forming part of the parasympathetic nervous system, your activity and staying in the synaptic cleft is regulated by hydrolysis catalyzed by acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) enzymes that modulate the levels of Ach in the nervous system. The outlook for new targets cholinesterase inhibitors has stimulated research using bioactive compounds of natural products and also the use of an animal model that provides better understanding of the mechanisms of cognitive development. Because they are microorganisms that produce secondary given this, metabolites of great importance for bioprospecting, a study of the anticholinesterase activity of compounds isolated from the endophytic fungus Phomopsis sp. (PE) associated with mangabeira (Hancornia speciosa). Furthermore, it was investigated the effect of menthol on the adult zebrafish memory in the passive avoidance test. The menthol was selected taking to account the screening conducted by our research group in previous work, where this compound showed potent anticholinesterase activity. In the search for promising compounds to anticholinesterase drugs, the present study aimed to evaluate the in vitro activity of the crude extract of the fungus, as well as their isolated compounds 5-methyl mellein (1), nectriapyrone (2), tyrosol (3) and tryptophol (4) in AChE and BuChE in vivo evaluation the effect of menthol on the acquisition of learning and memory consolidation. In all assays were obtained encouraging results. The crude extract of PE and its isolated compounds were effective to inhibit cholinesterase, and the tryptophol (4) was the most promising because it showed dual action on the enzymes being selective to BuChE. The study of exposure to menthol zebrafish showed that this compound produces no effect on memory. On the other hand, at all doses tested menthol reverses amnesia induced by scopolamine. This study, therefore, demonstrated the potencial use of these compounds isolated from PE as source of novel agents for the treatment of AD and that menthol may be indicated as therapeutic alternative for the treatment of memory deficits.